Beyond the beach: a look into the community value of the Shark Spotters Organisation - Besser, Maxwell (Department of Environmental and Geographical Science, 2025)
The Shark Spotter organisation operates in the False Bay area of Cape Town, South Africa. Their main goal is to help minimise the interactions between beach goers and marine megafauna, with special attention given to sharks. Their employees do this through an exclusion net and a flag signaling system. Shark Spotters provides employees opportunities to increase their knowledge and skills in areas that can be used outside of their employment duties to create supplemental income sources and increase community health. The purpose of this study was to determine the number of persons each Shark Spotter employee supports with their income and investigate if the skills developed through Shark Spotters are being used outside of the employment duties to contribute to the local community or informal economy. This study used a combination of qualitative and quantitative interviews to gather this data, which was analysed using descriptive statistics and thematic analyses, respectively. The data was inconclusive about the specific number of dependents each employee had, as households were communal, and they also sometimes contributed to a secondary residence, but showed that their income was essential for the livelihood of their households. The skills being gathered by the employees were shown to not be used outside of their work duties due to a range of factors that include a lack of an available market, a communal spirit that doesn't promote financial gain from neighbours, and violent criminal activity. Since employees were limited in the ability to use the skills gained through Shark Spotters outside of their employment, there was a great interest in increasing non-marketable knowledge through environmental education to participate in local research efforts. If Shark Spotters wish to improve the ability of their employees to contribute to their community or participate in the informal economy, partnerships would need to be made with other organisations to address the complex barriers to entry.